Preparation of K2CO3-activated biochar from peanut shell and Chlorella for enhanced carbamazepine adsorption: Performance, mechanism, and reusability - Zhenzhen Li; Jiayu Wu; Ting Cheng; Liling Zhou; Yujia Yang (Journal of Environmental Management, 2026)

Corrigendum to “Long-term exposure to fine particulate matter constituents and the prognosis of oral cancer patients: A prospective study in Southeastern China” [J Hazard Mater 487 (2025) 137304] - Peng Hu; Liling Shen; Ge Chen; Weiyi Yang; Yanmei Ji; Baochang He; Hualiang Lin (Journal of Hazardous Materials, 2026)

Effects of ultrasound, blanching, and ethanol pretreatments on drying characteristics, microstructure, and quality of apricots using hot air-assisted radio frequency energy - Jiahong Yuan; Dongsheng Hu; Qianjie Xiong; Rui Li; Liling Yang; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2026)

Engineering Agriophyllum squarrosum starch-butyric acid complexes with functional properties via ionic liquids-ultrasonication synergy - Shaopan Cao; Yuxin Yang; Yongye Wu; Yang Hu; Jie Zhang; Shilong Cheng; Si Wu; Yang Liu; Liling Zhang; Ling Jiang (Food Research International, 2026)

When health labels increase indulgent food purchase intention - Xiaoke Yang; Liling Zheng; Shen Duan; Wenqing Zheng; Ziyang You; Liuyang Yao (Food Quality and Preference, 2026)

Caffeic acid-grafted high-amylose maize starch for self-stabilizing emulsion gels: efficient encapsulation and protection of pterostilbene - Liling Fu; Yanan Ren; Conghe Zhang; Wei Yang; Guixiang Zhou; Tian Xu; Changhong Liu; Lei Zheng (Food Chemistry, 2026)

Aerobic and anaerobic degradation of BDE-47 by facultative anaerobe Pseudomonas sp. QS-1: Pathway, product toxicity, and bio-augmentation remediation - Xin Qi; Ziwei Wang; Qixin Xia; Xiuping Liang; Guiyin Wang; Changlian Xu; Guochun Lv; Junzhuo Cai; Zhang Cheng; Zhanbiao Yang; Liling Wang; Xiaoxun Xu; et al. (Process Safety and Environmental Protection, 2026)

A novel Pickering emulsion stabilized solely by n-butyric acid-modified high-amylose corn starch for resveratrol delivery - Liling Fu; Yanan Ren; Conghe Zhang; Wei Yang; Qisheng Tian; Guixiang Zhou; Tian Xu; Changhong Liu; Lei Zheng (Carbohydrate Polymers, 2026)

Multilayered regulatory control of compound leaf development - Liangliang He; Liling Yang; Weiyue Zhao; Jianghua Chen (Current Opinion in Plant Biology, 2026)

A novel marine biomineralization bacterium Exiguobacterium sp. 9–2: Inducing calcium carbonate precipitation with ferric ion-mediated facilitation - Tingting Zhu; Liling Xu; Zhengli Wu; Lijing Yang; Zhenlun Song (Journal of Environmental Chemical Engineering, 2025)

Assessment of potentially toxic elements (PTEs) in surface and groundwater of volcanic and granite regions of Hainan Island, China: Pollution status, sources, and health risk evaluation - Jianzhou Yang; Yong Li; Shengyue Liang; Min Zhang; Jingjing Gong; Yufang Li; Qiankun Yan; Xiaohui Sun; Zuyang Xu; Xueju Liu; Shuqi Hu; Jianweng Gao; et al. (Environmental Geochemistry and Health, 2025)

Spatiotemporal evolution and attribution of urban exposure to compound precipitation and wind speed extremes in China since 1980 - Liling Chu; Chao He; Yang Jiang (Anthropocene, 2025)

Passion fruit peel pectin improves glucose and lipid metabolism in high-fat diet-induced obesity through gut microbiota and insulin sensitivity regulation - Ying Ju; Liling Huang; Hailing Luo; Yongcai Huang; Xianya Huang; Ge Chen; Jie Gui; Shengli Lin; Xuzhou Liu; Liu Yang (Food Bioscience, 2025)

Effect of salt valence and ionic strength on the rheology and 3D printing performance of walnut protein emulsion gels - Guohua Li; Bo Wang; Liling Yang; Weiqiao Lv; Hongwei Xiao (Food Hydrocolloids, 2025)

Mediation role of gut microbiota in the association between ambient fine particulate matter components and cardiovascular disease: Evidence from a China cohort - Shaokun Yang; Rui Yu; Fen Yang; Jiawei Li; Lele Wang; Gonghua Wu; Liling Chen; Tingting Yang; Zhuoma Duoji; Yanjiao Wang; Xufang Gao; Yuanyuan Liu (Environmental Research, 2025)

A simplified in-situ extraction method for pyrethroid pesticides from complex food matrix through pore-switching response based on rationally designed Zr-MOFs with anti-interference performance - Lei Huang; Qianwen Yang; Yujie Yang; Tai Ye; Hui Cao; Liling Hao; Xiuxiu Wu; Fei Xu (Chemical Engineering Journal, 2025)

Effects of innovative dry-blanching on moisture, cell wall structure, physicochemical properties and volatile compounds of microwave infrared coupled dried ginger (Zingiber officinale roscoe) - Shiyu Zeng; Bingzheng Li; Liling Yang; Weiqiao Lv; Hongwei Xiao (Food Chemistry, 2025)

pH stability improved electrochemical biosensor based on dopamine/aptamer imprinted polymer modified electrodes for simultaneous detection of four toxic metal ions - Jiahao Sha; Liling Hao; Xinyu Fang; Nianxin Zhu; Yihang Yang; Kaiming Peng; Tai Ye; Hui Cao; Huajie Gu; Fei Xu (Food Control, 2025)

Long-term exposure to fine particulate matter constituents and the prognosis of oral cancer patients: A prospective study in Southeastern China - Peng Hu; Liling Shen; Ge Chen; Weiyi Yang; Yanmei Ji; Baochang He; Hualiang Lin (Journal of Hazardous Materials, 2025)

Role of heat pretreatment and transglutaminase treatment on the gelling properties of pea protein - Suqi Yang; Liling Tao; Zihang Yan; Kefan Ouyang; Qin Zhang; Yuanyuan Feng; Qiang Zhao (Food Bioscience, 2025)

Spatial single-cell maps reveal ST6GAL1 promoting ovarian cancer metastasis - Lan-hui Qin; Zijian Jiang; Chongze Yang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Jin-yuan Liao; Liling Long (Glycoconjugate Journal, 2025)

Microbiologically influenced corrosion inhibition of carbon steel by a novel bacterium, Photobacterium sp., in simulated marine environment - Tingting Zhu; Liling Xu; Lijing Yang; Pingping Zhao; Xinglong Zhu; Zhengli Wu; Zhenlun Song (Environmental Research, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

In-field grading and sorting technology of apples: A state-of-the-art review - Jiangfan Yu; Zhao Zhang; Yifei Li; Wanjia Hua; Xinyu Wei; C. Igathinathane; Mustafa Mhamed; Wenqiang Zhang; Xiaoqiang Jiao; Liling Yang; Man Zhang; Han Li (Computers and Electronics in Agriculture, 2024)

Effect of κ-carrageenan on physicochemical and 3D printing properties of walnut protein-stabilized emulsion gel - Guohua Li; Bo Wang; Weiqiao Lv; Liling Yang; Hongwei Xiao (Food Hydrocolloids, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Optimization of Cr(VI) ion-imprinted polymer with imidazole derivatives as functional monomers and its binding mechanism - Mengyuan Huang; Yuanyuan Yang; Hui Cao; Min Yuan; Tai Ye; Liling Hao; Jinsong Yu; Fengqin Yin; Fei Xu; Xiuxiu Wu (Journal of Environmental Chemical Engineering, 2024)

Investigating the impact of watershed and local environmental variables on the spatial distribution, composition and functional diversity of benthic algal communities in the upper Red River Basin, China - Kejian He; Xuekai Feng; Changming Chen; Yu Han; Xiaoxiao Ji; Yangyidan He; Liling Yang; Yuan He; Xingcan Chen; Liqin Yan (Aquatic Sciences, 2024)

Ultrasonic preparation of citral/hydroxypropyl-β-cyclodextrin inclusion complex: Application as a potential antifungal preservative in strawberry storage - Dan Shen; Xia Chang; Liling Zhou; Dandan Hao; Zhongxiang Fang; Yang Shan; Lvhong Huang; Gaoyang Li (Food Control, 2024)

Differential responses of macroinvertebrates and phytoplankton to river health status in different habitats - Kejian He; Changming Chen; Yangyidan He; Xuekai Feng; Hong Tang; Liling Yang; Yuan He; Wenna Lyu (Aquatic Sciences, 2024)

Optimizing directional recovery of high-bioavailable phosphorus from human manure: Molecular-level understanding and assessment of application potential - Yao Xu; Nan Li; Libin Yang; Tongcai Liu; Shaoze Xiao; Liling Zhou; Dapeng Li; Jiabin Chen; Yalei Zhang; Xuefei Zhou (Water Research, 2023)

Vertical and seasonal dynamics of bacterial pathogenic communities at an aged organic contaminated site: Insights into microbial diversity, composition, interactions, and assembly processes - Zhirui Qin; Zhenhua Zhao; Liling Xia; Guangwen Yu; Aihua Miao; Zijun Yang (Journal of Hazardous Materials, 2023)

Broad humoral immunity generated in mice by a formulation composed of two antigens from the Delta variant of SARS-CoV-2 - Yadira Lobaina; Rong Chen; Edith Suzarte; Panchao Ai; Vivian Huerta; Changyuan Tan; Liz Alvarez-Lajonchere; Yang Liling; Alexis Musacchio; Ricardo Silva; Gerardo Guillén; Jiang Zaixue; et al. (Archives of Virology, 2023)

Active packaging coatings based on agarose caffeate: Preparation, characterisation, and application in grass carp (Ctenopharyngodon idellus) preservation - Liling Fu; Yi Ru; Qinglin Hong; Yonghui Zhang; Huifen Weng; Qiuming Yang; Qiong Xiao; Anfeng Xiao (Food Packaging and Shelf Life, 2023)

NCX2 Regulates Intracellular Calcium Homeostasis and Translocation of HIF-1α into the Nucleus to Inhibit Glioma Invasion - Hongyuan Liu; Ju Yu; Liling Yang; Pengcheng He; Zongping Li (Biochemical Genetics, 2023)
Glioma is the most common tumor of the central nervous system, and its poor prognosis can be linked to hypoxia and gene inactivation. Na + /Ca 2+ exchanger 2 (NCX2) is expressed only in the normal brain and not in other tissues or glioma. We constructed a hypoxic microenvironment to more accurately understand the effect of NCX2 in glioma. Our previous experiments confirmed that NCX2 inhibited the growth of U87 cells in nude mice, indicating that NCX2 is a potential tumor suppressor gene. Malignant tumor cells are often exposed to an anoxic environment. To more accurately understand the effect of NCX2 in glioma, we constructed a hypoxic microenvironment. To detect the localization of NCX2 in transfected U87 cells, immunofluorescence was used. We tested the function of NCX2 in glioma, i.e., how it contributes to the cytosolic Ca 2+ homeostasis by X-Rhod-1. We tested the cell proliferation of NCX2 in glioma in hypoxic using Cell counting kit-8 (CCK8). Cell migration and invasion were evaluated in 24-well transwell matrigel-coated or non-matrigel-coated in hypoxia. NCX2 promoted the proliferation of U87 cells in the hypoxic microenvironment. It inhibited the invasion and migration abilities of U87 cells. We demonstrated that NCX2 was located on the cell membrane and that it reduced intracellular Ca 2+ levels and reactivated P53 and PTEN. We further demonstrated that NCX2 impaired cell invasion through the HIF-1α pathway in glioma. The results indicated that NCX2 plays a key role in glioma formation and tumor invasion functionality.

Continued evolution of the Eurasian avian-like H1N1 swine influenza viruses in China - Fei Meng; Yan Chen; Zuchen Song; Qiu Zhong; Yijie Zhang; Chuanling Qiao; Cheng Yan; Huihui Kong; Liling Liu; Chengjun Li; Huanliang Yang; Hualan Chen (Science China Life Sciences, 2023)

A review on chemical and physical modifications of phytosterols and their influence on bioavailability and safety - Simin Feng; Liling Wang; Ping Shao; Peilong Sun; Chung S. Yang (Critical Reviews in Food Science and Nutrition, 2022)

CircRNA expression profiling and bioinformatics analysis indicate the potential biological role and clinical significance of circRNA in influenza A virus-induced lung injury - Jiajia Wang; Yanbing Zhang; Fengfeng Zhu; Liling Chen; Yao Wei; Qingqing Zhu; Junhong Jiang; Jian-an Huang; Qiang Guo; Xinjing Yang (Journal of Biosciences, 2021)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Liangyi Gao extends lifespan and exerts an antiaging effect in Caenorhabditis elegans by modulating DAF-16/FOXO - Liling Zeng; Chen Sun; Zhong Pei; Tianchan Yun; Shaoyi Fan; Simei Long; Tengteng Wu; Ziwen Chen; Zhimin Yang; Fuping Xu (Biogerontology, 2019)

Correction to: Strategies of Drug Transporter Quantitation by LC-MS: Importance of Peptide Selection and Digestion Efficiency - Buyun Chen; Liling Liu; Hoangdung Ho; Yuan Chen; Ze Yang; Xiaorong Liang; Jian Payandeh; Brian Dean; Cornelis E. C. A. Hop; Yuzhong Deng (The AAPS Journal, 2018)

Soil heavy metal pollution and risk assessment associated with the Zn-Pb mining region in Yunnan, Southwest China - Xianfeng Cheng; Tomas Danek; Jarmila Drozdova; Qianrui Huang; Wufu Qi; Liling Zou; Shuran Yang; Xinliang Zhao; Yungang Xiang (Environmental Monitoring and Assessment, 2018)

Strategies of Drug Transporter Quantitation by LC-MS: Importance of Peptide Selection and Digestion Efficiency - Buyun Chen; Liling Liu; Hoangdung Ho; Yuan Chen; Ze Yang; Xiaorong Liang; Jian Payandeh; Brian Dean; Cornelis E. C. A. Hop; Yuzhong Deng (The AAPS Journal, 2017)

Characterization of an efficient catalytic and organic solvent-tolerant azoreductase toward methyl red from Shewanella oneidensis MR-1 - Yuyi Yang; Liling Lu; Fen Gao; Yuhua Zhao (Environmental Science and Pollution Research, 2013)

Photocatalytic degradation of phenol with mesoporous TiO2−xBx - Leyan Xiong; Longzhen Zheng; Jingpeng Xu; Dan Zheng; Junhua Li; Xinjia Li; Juan Sun; Qiang Liu; Liling Niu; Shaoming Yang; Jian Xia (Environmental Chemistry Letters, 2011)